Cognitive function and disability in late life: an ecological validation of the 10/66 battery of cognitive tests among community‐dwelling older adults in South India. (17th December 2015) - Krishna, Murali; Beulah, Eunice; Jones, Steven; Sundarachari, Rajesh; A, Saroja; Kumaran, Kalyanaraman; Karat, S. C.; Copeland, J. R. M.; Prince, Martin; Fall, Caroline
Abstract : Background: The 10/66 Dementia Research Group developed and validated a culture and education fair battery of cognitive tests for diagnosis of dementia in population‐based studies in low‐income and middle‐income countries including India. Aims: This study examined the association between individual domains of the 10/66 battery of cognitive tests and 'disability' and 'functional impairment' in community‐dwelling older adults in South India. Methods: One hundred twenty‐nine adults aged 60–90 years residing in Karunapura, in the city of Mysore, were interviewed in their own homes. Cognitive functioning was measured by administering the 10/66 battery of cognitive tests that composes of Community Screening Instrument for Dementia (CSI'D' COGSCORE), verbal fluency (VF) and word list memory recall (WLMR). A reliable informant was interviewed to ascertain if the subject's cognitive problems have resulted in functional impairment. Disability was measured by WHO Disability Schedule‐II (DAS). Results: The women had significantly lower CSI'D' COGSCORE score when compared with men ( p  = 0.002). The presence of 'functional impairment' resulting from cognitive decline was significantly associated with lower scores on VF ( p  = 0.03), WLMR ( p  = 0.03) and CSI'D' COGSCOREs ( p  < 0.01). There was a significant inverse association between WHO DAS II score and WLMR ( p  = 0.004), VF (0.006) and CSI'D' COGSCORE scores ( p  ≤ 0.001) even after adjusting for self‐reported ischaemic heart disease, stroke, chronic obstructive airway disease, hypertension and diabetes. Conclusions: Lower scores on individual domains of the 10/66 battery of cognitive tests are associated with higher levels of disability and functional impairment in community‐dwelling older adults. These culture and education fair tests are suitable for use in population‐based research in India. Copyright © 2015 John Wiley & Sons, Ltd.